Hubungan Konsumsi Herbal dengan Kepatuhan Minum Obat Standar pada Pasien Hipertensi di Wilayah Kerja Puskesmas Lempake Samarinda - Safitri, Wenda; Ismail, Sjarif; Isnuwardana, Ronny (Jurnal Kesehatan Andalas, 2023)
It is crucial for patients with hypertension to always control their blood pressure by consuming medicines for hypertension, the morbidity and mortality rates will be hopefully reduced. Medication adherence is necessary in order to reach the target of controlling blood pressure. There are a lot of causes affecting medication adherence, one of which is the consumption of herbal remedies. Objective: To investigated the correlation between the consumption of herbal remedies and medication adherence among patients with hypertension at Lempake Public Health Centre in Samarinda. Methods: The research design was analytical observational with a cross-sectional approach. The statistical analysis used Chi-Square test. The data were collected through interviews with 94 respondents. They were selected using convenience sampling and also asked to fulfill the identity form and MMAS-8 questionnaire. Results: Most respondents at Lempake Public Health Centre in Samarinda consumed herbal remedies (42.6%), but their medication adherence was low (82.9%). The significant p-value was 0.008 based on the statistical analysis. Conclusion: There is a significant correlation between the consumption of herbal remedies and medication adherence among patients with hypertension at Lempake Public Health Centre in Samarinda.Keywords: Â herbal, hypertension, medication adherence, MMAS-8